Anthropometric comparison between young Estonian and Chinese swimmers - Cicchella, A.; Jidong, L.; Jürimäe, T.; Zini, M.; Passariello, C.; Rizzo, L.; Stefanelli, C. (Journal of Human Sport & Exercise, 2009)
Due to the progressive lowering of the age of peak performance among swimmers, it became important to better understand the factors influencing performance in prepuberal boys and girls. Aim of this study is to compare two different racial/ethnic groups of young swimmers, one from Nord-Europe, Estonia (Tartuma Region), and the other from China (Shanghai District) in order to assess existing differences in respect to body dimension, body fat, technical parameters of swimming performance and maximum lactate production. 26 Estonian and 7 Chinese female and 25 Estonian and 10 Chinese male, from two swimming schools, took part in the study. Anthropometric parameters were measured in accord with ISAK guidelines. BMI, Stroke Index, Stroke Length, mean velocity on a 200 m freestyle all out, and blood lactate after three minutes were measured. Significant differences exist in anthropometry between Nord-European and Asian young swimmers. These differences are more pronounced in female, with higher fat tissue in Nordic girls. Leg lengths are different between Chinese and Estonian girls having the Estonian longer legs. Hands lengths are different both in male and in female subjects. Being the Chinese groups of higher level of performance (higher mean velocity in the 200 m freestyle, such differences seems not to be as major determinants of the performance, also if they are often indicated as determinants of buoyancy and stroke efficiency.